CONSUMER BEHAVIOR OF GENERATION Z STUDENTS: THE INFLUENCE OF USING LAZADA E-COMMERCE, PROMOTIONS AND SOCIAL MEDIA (CASE STUDY OF TRISAKTI INSTITUTE OF TOURISM STUDENTS) - Anita Swantari; Michael Khrisna Aditya; Purwanti Dyah Pramanik (International Journal Management and Economic, 2025)
The rapid development of e-commerce, especially among Generation Z, has changed consumption patterns, especially online shopping. Lazada, one of Southeast Asia's largest e-commerce platforms, is the leading choice for students, especially at the Trisakti Institute of Tourism. This research aims to analyze the influence of using Lazada, promotions and social media on the consumer behaviour of Generation Z students. The method used is quantitative descriptive research with surveys as a data collection technique by distributing questionnaires to 150 students who actively use Lazada. The research results show that using Lazada E-Commerce, promotions, and social media significantly contributes to students' consumptive behaviour. In conclusion, ease of access, attractive promotions, and social media influence encourage students to shop more frequently, potentially leading to overspending. It is recommended that students be wiser in managing expenses. Lazada provides education about financial management, and lecturers can increase awareness about the impact of consumer behaviour on students' economic well-being.